Past approaches and future challenges to the management of fire and invasive alien plants in the new Garden Route National Park - Tineke Kraaij; Richard Cowling; Brian van Wilgen (South African Journal of Science, 2011)
The recently established Garden Route National Park (GRNP) along the Cape south coast of South Africa occurs in a landscape where indigenous forests, fire-prone fynbos shrublands and fire-sensitive plantations of alien invasive trees are interspersed. We used the area as a case study in the challenges facing conservation managers in the achievement of biodiversity goals in a fire-prone environment. We explored the context within which fire management was practised during the past century by interviewing former catchment managers and reviewing forestry and catchment management policies. Mountain fynbos adjacent to plantations was subjected to burning regimes aimed at the protection of commercial timber resources rather than the preservation of fynbos biodiversity. Prescribed burning of fynbos adjacent to the plantations was typically done in multiple belt systems at rotations of about 4-8 years during spring, summer and autumn, to avoid the winter berg wind season. Such short-rotation and low-intensity fires favour resprouting graminoids over slow-maturing reseeders, and likely account for the compositional impoverishment observed in fynbos near plantations. Current and future challenges faced by the GRNP include (1) balancing conflicting fire management requirements for plantation safety against fynbos conservation; (2) the continual invasion of fynbos by fire-propagated alien pines sourced from plantations; (3) inadequate resources to redress the 'invasion debt' caused by the socio-economic legacy and past management neglect; and (4) fragmentation of land use between conservation and forestry threatening the sustainability of the region at large. We provide recommendations for management actions and research priorities to address these challenges.